2023
DOI: 10.1029/2022je007446
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Lava Flow Morphologies in the Stratigraphy of the Jezero Crater Floor

Abstract: We present a combined geomorphologic, multispectral, and geochemical analysis of crater floor rocks in Jezero crater based on data obtained by the Mast Camera Zoom and SuperCam instruments onboard the NASA Mars 2020 Perseverance rover. The combined data from this analysis together with the results of a comparative study with geologic sites on Earth allows us to interpret the origins of rocks exposed along the Artuby ridge, a ∼900 m long scarp of lower Máaz formation rocks. The ridge exposes rocks belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 88 publications
(263 reference statements)
3
25
0
Order By: Relevance
“…Earth‐based geochronology studies of the samples will help to determine the age of emplacement of these igneous members relative to one another and to the Isidis basin and Jezero crater‐forming events, as well as constraining the nature of Jezero resurfacing events and subsequent exhumation and erosion. The Máaz and Séítah formations are igneous in origin (e.g., Farley et al., 2022; Liu et al., 2022); Séítah represents an olivine‐rich cumulate formed from differentiation of a large melt or magmatic body, and the Máaz formation likely represents a separate series of lava flows emplaced on top of Séítah, with possible minor contributions from pyroclastic or airfall deposits (Alwmark et al., 2023). Geochronology and geochemical analysis of the returned samples will help to refine the petrologic histories of the Séítah and Máaz formations. Both the Máaz and Séítah formation rocks show evidence for multiple distinct episodes of aqueous alteration, although not in an extensive open system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earth‐based geochronology studies of the samples will help to determine the age of emplacement of these igneous members relative to one another and to the Isidis basin and Jezero crater‐forming events, as well as constraining the nature of Jezero resurfacing events and subsequent exhumation and erosion. The Máaz and Séítah formations are igneous in origin (e.g., Farley et al., 2022; Liu et al., 2022); Séítah represents an olivine‐rich cumulate formed from differentiation of a large melt or magmatic body, and the Máaz formation likely represents a separate series of lava flows emplaced on top of Séítah, with possible minor contributions from pyroclastic or airfall deposits (Alwmark et al., 2023). Geochronology and geochemical analysis of the returned samples will help to refine the petrologic histories of the Séítah and Máaz formations. Both the Máaz and Séítah formation rocks show evidence for multiple distinct episodes of aqueous alteration, although not in an extensive open system.…”
Section: Discussionmentioning
confidence: 99%
“…Rocks of the Máaz formation also exhibit flow-like morphologies (Figure 5d), vesicular textures (Figures 5e,9f,and 11d), and layering, particularly within the Artuby member (Figures 9f and 13d). A minor contribution from pyroclastic or aeolian materials, intercalated with lava flows, is possible for the Artuby member, as observations of thin, recessive layers framing more bulbous portions (e.g., Figure 9c) are difficult to attribute to effusive processes (Alwmark et al, 2023). Though initially considered part of the Séítah formation due to its geographic occurrence, the Content member may instead represent lava flows as well, based on its similar composition to upper Máaz (Section 5.1.2) and its pitted texture (Figure 17c), which is difficult to reconcile with a cumulate origin (Wiens et al, 2022).…”
Section: Igneous Originmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the in situ investigation of the dark floor unit (Alwmark et al., 2023; B. Horgan et al., 2022; Sun et al., 2022) revealed that the Máaz formation is layered and comprised of five different members, with different properties that could influence erosion and crater retention. The primary spatial extension of these sub‐units is not known even if some margin of potential lava flow may have been identified (Alwmark et al., 2023; B. Horgan et al., 2022). It may complicate the history we are presenting here: once exposed to bombardment, these different subunits may have eroded at different rates.…”
Section: Discussionmentioning
confidence: 99%